2018
DOI: 10.1016/j.midw.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of mindfulness-based childbirth and parenting courses for pregnant women and prospective fathers/partners within the UK NHS (MBCP-4-NHS)

Abstract: This research provides a clear rationale and justification for a large randomised control trial of this intervention within the NHS, which should include a more diverse population, across multiple centres and should explore both the potential health benefits for parents and infants/children as well as potential economic costs/benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 51 publications
3
36
2
Order By: Relevance
“…Like the protocol that will be used in the present study, this effect size was found in a recent RCT that used a modified MBCP program [24] compared to a TAU active standard childbirth preparation course with no mind-body components. This effect size is also similar to that obtained in other studies using other programs [44], a pilot study evaluating the effectiveness of MBCE [33], a cohort study assessing the MindBabyBody program [34], and a brief pilot adaptation based upon the MBCP program [9]. Considering a statistical power of 80%, a 5% significance level in a between-group interaction with a local alpha of 0.017 in the first test-using Benjamini-Hochberg's procedure-and a dropout rate in the range of 15%-20%, as has been observed in these types of studies [45], 61 participants are needed in each group, for a total sample size of 122 women.…”
Section: Sample Sizesupporting
confidence: 84%
See 1 more Smart Citation
“…Like the protocol that will be used in the present study, this effect size was found in a recent RCT that used a modified MBCP program [24] compared to a TAU active standard childbirth preparation course with no mind-body components. This effect size is also similar to that obtained in other studies using other programs [44], a pilot study evaluating the effectiveness of MBCE [33], a cohort study assessing the MindBabyBody program [34], and a brief pilot adaptation based upon the MBCP program [9]. Considering a statistical power of 80%, a 5% significance level in a between-group interaction with a local alpha of 0.017 in the first test-using Benjamini-Hochberg's procedure-and a dropout rate in the range of 15%-20%, as has been observed in these types of studies [45], 61 participants are needed in each group, for a total sample size of 122 women.…”
Section: Sample Sizesupporting
confidence: 84%
“…Among Spanish women, the prevalence of prenatal depressive symptoms is approximately 15% [7]. In addition, prenatal depression appears to affect men; thus, the importance of the presence of the partner in interventions tailored to improve couple wellbeing during pregnancy and postpartum is encouraged [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…G*Power software was used to calculate the number of participants required. Previous 8‐week mindfulness interventions in pregnant women showed medium‐to‐large effect sizes for anxiety (Cohen's d, 0.48‐0.66) and depression (Cohen's d, 0.42‐0.75) . Thus, at an effect size of d = 0.58, and allowing for a 25% attrition rate, the total number of participants required was 125 for a power of 0.8 …”
Section: Methodsmentioning
confidence: 95%
“…Several web-based mindfulness programs have been developed for informal caregivers of people with physical or mental conditions, showing improvement in caregiver stress and burden [47,48]. Finally, mindfulness for distressed pregnant women and their partners showed an effect on pregnant women's and their partners' anxiety and depression [49].…”
Section: Mindfulness Affecting Health Of Family Membersmentioning
confidence: 99%